Investigation of Cation Exchange Behaviors of FAxMA1−xPbI3 Films Using Dynamic Spin-Coating - Hyang Mi Yu (MDPI AG, 2021)
In this study, we fabricated and characterized uniform multi-cation perovskite FAxMA1−xPbI3 films. We used the dynamic spin-coating method to control the cation ratio of the film by gradually increasing the FA+, which replaced the MA+ in the films. When the FA+ concentration was lower than xFA ~0.415 in the films, the stability of the multi-cation perovskite improved. Above this concentration, the film exhibited δ-phase FAPbI3 in the FAxMA1−xPbI3 films. The formation of δ-phase FAPbI3 disturbed the homogeneity of the photoluminescence spatial distribution and suppressed the absorption spectral bandwidth with the increasing bandgap. The precise control of the cation ratio of multi-cation perovskite films is necessary to optimize the energy-harvesting performance.